Pulmonary embolism-related refractory out-of-hospital cardiac arrest and extracorporeal cardiopulmonary resuscitation: Prague OHCA study post hoc analysis - Pudil, Jan; Rob, Daniel; Smalcova, Jan; Smid, Ondrej; Huptych, Michal; Vesela, Michaela; Kovarnik, Tomas; Belohlavek, Jan (European heart journal. Acute cardiovascular care, 2023)
AIMS: Refractory out-of-hospital cardiac arrest (r-OHCA) in patients with pulmonary embolism (PE) is associated with poor outcomes. The role of extracorporeal cardiopulmonary resuscitation (ECPR) in this patient group is uncertain. This study aims to analyse clinical course, outcomes, and the effect of an invasive procedure, including ECPR, in a randomized population. METHODS AND RESULTS: A post hoc analysis of a randomized controlled trial (Prague OHCA study) was conducted to evaluate the effect of ECPR vs. a standard approach in r-OHCA. A subgroup of patients with PE-related r-OHCA was identified, and procedural and outcome characteristics, including favourable neurological survival, organ donation, and complications, were compared to patients without PE. Pulmonary embolism was identified as a cause of r-OHCA in 24 of 256 (9.4%) enrolled patients. Patients with PE were more likely to be women [12/24 (50%) vs. 32/232 (13.8%); P < 0.001] and presented more frequently with an initial non-shockable rhythm [23/24 (95.8%) vs. 77/232 (33.2%); P < 0.001], as well as more severe acidosis at admission [median pH (interquartile range); 6.83 (6.75-6.88) vs. 6.98 (6.82-7.14); P < 0.001]. Their favourable 180-day neurological survival was significantly lower [2/24 (8.3%) vs. 66/232 (28.4%); P = 0.049], but the proportion of accepted organ donors was higher (16.7 vs. 4.7%, P = 0.04). CONCLUSION: Refractory out-of-hospital cardiac arrest due to PE has a different presentation and inferior outcomes compared to other causes but may represent an important source of organ donations. The ECPR method did not improve patient outcomes.
Keywords: kardiopulmonální resuscitace; Out-of-Hospital Cardiac Arrest; Male; retrospektivní studie; Pulmonary Embolism; zástava srdce mimo nemocnici; cardiac arrest; mužské pohlaví; pulmonary embolism; mimotělní membránová oxygenace; lidé; Cardiopulmonary Resuscitation; ženské pohlaví; Humans; Extracorporeal Membrane Oxygenation; organ donorship; Retrospective Studies; extracorporeal cardiopulmonary resuscitation; Female; plicní embolie